1971
DOI: 10.1139/b71-152
|View full text |Cite
|
Sign up to set email alerts
|

Pigments, polysaccharides, and photosynthetic products of Phaeosaccion collinsii

Abstract: 1971. Pigments, polysaccharides, and photosynthetic products of Phaeosaccion colli~rsii. Can. J. Bot. 49: 1067-1074. Zoospores of Phaeosaccion collinsii averaged 70 p3 and contained total N 2.24 pg, DNA 0.19, and chlorophyll a 0.62 pg per spore. In addition, chl c, "cis"-8-carotene, fucoxanthin, and violaxanthin were principal pigments and a minor unidentified carotene was present.Photosynthetic rates of zoospores were 0.37 X 10-l2g C per spore per hour, or 0.59 mg C per mg chl a per hour at 5". The principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Based on fine-structural Phycological Research 1999;47: 53-60 Immunogold-labeling analysis of alginate distributions in the cell walls of chromophyte algae features, especially those of flagellar root systems, Chrysomeridales including Giraudyopsis stellifera Dangeard were suggested to be a direct ancestor of the Phaeophyceae (O'Kelly and Floyd 1985;O'Kelly 1989). However, the absence of alginates in Phaeosaccion collinsii Farlow (Craigie et al 1971) does not support this notion, and furthermore, recent molecular studies have indicated a closer relationship to the Phaeophyceae and Xanthophyceae (Ariztia et al 1991;Andersen et al 1993Andersen et al , 1998.…”
Section: Introductionmentioning
confidence: 95%
“…Based on fine-structural Phycological Research 1999;47: 53-60 Immunogold-labeling analysis of alginate distributions in the cell walls of chromophyte algae features, especially those of flagellar root systems, Chrysomeridales including Giraudyopsis stellifera Dangeard were suggested to be a direct ancestor of the Phaeophyceae (O'Kelly and Floyd 1985;O'Kelly 1989). However, the absence of alginates in Phaeosaccion collinsii Farlow (Craigie et al 1971) does not support this notion, and furthermore, recent molecular studies have indicated a closer relationship to the Phaeophyceae and Xanthophyceae (Ariztia et al 1991;Andersen et al 1993Andersen et al , 1998.…”
Section: Introductionmentioning
confidence: 95%
“…Calculating from this, the annual spore production of an E. maxima sporophyte will have a volume of only 5.27 cm 3. Also, if we assume that the relationship between volume and carbon content of unicellular plankton organisms (Holm-Hansen, 1969) holds for kelp zoospores (this has been previously used for zoospores of the Chrysophyte Phaeosaccion collinsii Farlow by Craigie et al, 1971) we can estimate that the 9.36 x 1017 spores per year contain 3.66 x 107 gC = 36.6 tonnes of carbon produced per year per southern Benguela region (or 0.17 tonnes of carbon per year per km of coastline). Using the kelp-production data put forward by Jarman & Carter (1981) we estimate that for a total 21,978 tonnes of carbon produced by Ecklonia plants in the southern Benguela region annually, measured as growth increment, a further 36.6 tonnes C is released into the system as zoospores.…”
Section: Discussionmentioning
confidence: 99%
“…Craigie and McLachlan (1964) showed that glycerol accumulated in the marine green alga Dunaliella tertiolecta photosynthesizing under salinity stress. Photosynthetic products reported included a suite of galactosyl glycerols in red algae (Majak et al 1966;Craigie et al 1968), unusual cyclitols in red algae and chrysophytes (Ramanathan et al 1966;Craigie 1969Craigie , 1974Laycock and Craigie 1970;Craigie et al 1971) and mannitol in prasinophycean and chrysophycean algae . The effects of carboxylic acids on growth and photosynthesis of Haematococcus pluvialis was reported by McLachlan and Craigie (1965) as was photosynthesis in algae containing chlorophyll b (McLachlan and Craigie 1967).…”
Section: Ralph Lewinmentioning
confidence: 99%